Pengembangan E-LKPD Berbasis Keterampilan Proses Sains pada Materi Sistem Gerak - Sahid, Muhammad Rifky Haekal; Arsal, Andi Faridah; Adnan, Adnan (Biology Teaching and Learning, 2021)
Abstract. This study aims to develop teaching materials in the form of electronic student worksheets based on science process skills in class XI high school motion system material. This research is research and development with ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). The electronic LKPD teaching materials that were developed were tested for validity by 2 expert lecturers and tested for practicality by teachers and students. The subjects of this study were 30 students and 2 biology teachers at UPT SMA Negeri 4 Parepare who were selected for a limited trial of the developed electronic LKPD teaching materials. Data collection techniques were carried out through filling out practicality questionnaires by teachers and students. The results showed that the developed electronic LKPD was declared valid with an average score of 4.7. LKPD is declared practical based on the results of the teacher's response analysis with an average score of 93.98% and the results of the student response analysis with an average score of 79.19%. Based on the results of this study, it can be concluded that the electronic student worksheets based on science process skills in the motion system material for class XI SMA are valid and practical.Keywords: worksheet, electronic, addie, valid, practical